Ni-based bimetallic catalysts for hydrogen production via (sorption-enhanced) steam methane reforming - Wang, Siqi; Shen, Ziqi; Osatiashtiani, Amin; Nabavi, Seyed Ali; Clough, Peter T. (Elsevier, 2024)
The catalytic performance of a monometallic Ni/Al2O3 and three bimetallic catalysts (Ni3M1/Al2O3, with M = Cu, Fe, and Ge) for the (sorption-enhanced) steam methane reforming reaction was evaluated. Ni3Cu1/Al2O3 was found to be the optimal catalyst in terms of methane conversion, hydrogen yield, and purity. Ge also has a promoting effect on the monometallic Ni catalyst, whereas the addition of Fe negatively influenced its performance. Physico-chemical characterization of the materials indicated the formation of alloys upon activation of the materials with hydrogen. The addition of Cu increased the surface area and metal dispersion, and improved the overall morphology of the catalyst. The experimental observations were also supported by a numerical study combining Density Functional Theory-based calculations and Microkinetic modelling of the SMR process. Ni3Cu1 and Ni3Ge1 were calculated to have a similar level of catalytic activity as Ni, whereas Ni3Fe1 was unsuitable for the reaction. The SMR reaction was further improved by adding calcium oxide as the CO2 sorbent, which increased methane conversion, CO selectivity, hydrogen yield, and hydrogen purity. The highest methane conversion of 97 % was achieved by Ni/Al2O3 and Ni3Cu1/Al2O3 at 700 °C.
Keywords: Bimetallic catalyst; Hydrogen production; Steam methane reforming; Sorption-enhanced steam methane reforming; Microkinetic modelling